The world's greatest small arms an illustrated history - McNab, Chris 1970- (Amber Books, 2015)
"This book features 52 of the most important guns of the last 140 years. Beginning with the Gatling Model 1878, the precursor of the machine guns that came to dominate twentieth century warfare, the volume covers all the major types used in World War I, World War II and the Cold War, before coming up to date with the latest specialist weapons, such as the M110 sniper rifle and FN SCAR assault rifle."